Impact of Universal Donor History Questionnaire in Pre-Donation Deferrals a Tertiary Care Hospital Experience - Farhan Ahmed Shaikh, Aqsa Noureen, Rukhsana Saboor, Sidrah, Azhar Ali, Kiran Memon, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research was to better understand the factors that lead to pre-donation deferral at a tertiary care hospital’s Blood bank. Understanding the factors that lead donors to decline can inform more effective selection criteria. Study Design: Cross-sectional/Descriptive study Place and Duration: Diagnostic and research laboratory Liaquat university of Medical and Health Sciences Jamshoro Hyderabad. January 2022-December 2022 Methods: This study comprised of 2200 donors at blood bank of LUMHS. The UDHQ included 25 questions to assess donors’ backgrounds in regards to things like injections, medicines, time since last donation, tattoos, general health, dental work, sexual relationships, malaria/T.B., surgery, jaundice, vaccination, positive viral markers, etc. Haemoglobin (Hemacue 50/Diaspect Hb with daily quality control), Heart rate/rhythm, Blood pressure, Body temperature, Weight/Height, and Jaundice were all part of the physical exam. Results: There were majority 1578 (71.7%) males and 622 (28.3%) female donors among all cases. Donors mean age was 26.12±9.88 years and mean weight was 61.3±8.49 kg. 1435 (65.2%) cases were from urban areas. Among all, 1650 (75%) donors were accepted and 550 (25%) donors were deferral. Most common cause of deferral was low hemoglobin followed by anemia, HCV, HBV, inappropriate pulse rate, low BP, jaundice, active infection, malaria, syphilis, allergy, aspirin intake, drugs, last donation, skin/eye colour and sexual relationship. There were 1870 (85%) cases of replacement donors among all cases. Conclusion: The selection of healthy blood and the reduction of donor injury will be made possible by a thorough pre-donation screening interview and physical examination. Our setup has a somewhat higher blood donor deferral rate because to stringent donor sector requirements and extra attention paid to donor selection processes. The increased replacement donor deferral rate is a result of refusals for past injection history and poor hemoglobin levels. Keywords: Donors, Deferrals, Hemoglobin, Infection, HCV